How stakeholder influence corrupted public leadership in tackling the Covid-19 outbreak in Ischgl - Geyer, Jessica (Organizational corruption, crime and COVID-19, 2025)
The outbreak of Covid-19 called for responsible leadership and management of the diverse stakeholders affected, including attention to the sentiments of key stakeholder groups. Our study focuses on public leadership in the context of the massive outbreak of Covid-19 in the Tyrolian ski resort of Ischgl in March 2020. We quantitatively analyze how (ir)responsible leadership evolved in this case over time in relation to the sentiments of relevant stakeholders. We then qualitatively analyze the turning points in the observed patterns to identify causal links between stakeholder sentiments and (ir)responsible leadership. We find that only local businesses expressed persistently positive sentiments towards public leadership in the crisis, while tourists, residents and most other stakeholder groups expressed predominantly negative sentiments. Our findings indicate that businesses misused their organizational power by downplaying the crisis in interactions with governmental actors through informal and opaque networks, illegitimately gaining a stronger influence than stakeholder salience theory would predict. Although negative sentiments prompted more responsible leadership at times, this proved unsustainable. Our study yields valuable insights for management students and practitioners into the detrimental effects of informal and arguably corrupt stakeholder management practices in the context of Covid-19.